2020
DOI: 10.1111/nph.17075
|View full text |Cite
|
Sign up to set email alerts
|

A highly differentiated region of wheat chromosome 7AL encodes a Pm1a immune receptor that recognizes its corresponding AvrPm1a effector from Blumeria graminis

Abstract:  Pm1a, the first powdery mildew resistance gene described in wheat, is part of a complex resistance (R) gene cluster located in a distal region of chromosome 7AL that has suppressed genetic recombination.  A nucleotide-binding, leucine-rich repeat (NLR) immune receptor gene was isolated using mutagenesis and R gene enrichment sequencing (MutRenSeq). Stable transformation confirmed Pm1a identity which induced a strong resistance phenotype in transgenic plants upon challenge with avirulent Blumeria graminis (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 69 publications
1
94
0
2
Order By: Relevance
“…S9). These features have been described for numerous Blumeria effectors, including all functionally characterized AVR proteins in wheat mildew (18, 20, 21). Using an in silico modelling approach based on IntFOLD5.0, we found that AVRPM17 is predicted to exhibit a ribonuclease-fold (pvalue = 1.145E-4), consisting of a single α-helix and three β-strands (Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…S9). These features have been described for numerous Blumeria effectors, including all functionally characterized AVR proteins in wheat mildew (18, 20, 21). Using an in silico modelling approach based on IntFOLD5.0, we found that AVRPM17 is predicted to exhibit a ribonuclease-fold (pvalue = 1.145E-4), consisting of a single α-helix and three β-strands (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…In wheat powdery mildew recent studies using map-based cloning, GWAS and effector benchmarking approaches have identified several avirulence genes, among them AvrPm3 a2/f2 , AvrPm3 b2/c2 and AvrPm3 d3 recognized by Pm3a/Pm3f, Pm3b/Pm3c and Pm3d respectively (17, 18). Sequence analysis of wheat mildew Avr genes revealed that they all encode small secreted candidate effector proteins (17, 18, 20, 21) and exhibit high levels of sequence variation on a population level including the independent evolution of numerous gain of virulence alleles by diverse molecular mechanisms (17, 18, 20, 22). The identification and functional characterization of mildew avirulence genes has therefore significantly broadened our understanding of race-specific resistance and resistance gene breakdown in the wheat – mildew pathosystem.…”
Section: Main Textmentioning
confidence: 99%
“…S1, Table S4). Therefore, we used the functional molecular marker (FMM) Pm1aSTS1 (Hewitt et al 2020) to genotype G18-16, but it did not yield any amplicons, suggesting that PmG16 is not allelic to Pm1a. Moreover, we found that a third NLR, TRIDC7AG077150.1, gave the highest BLAST scores for the previously cloned Pm60 gene located in syntenic location in chromosome 7L of T. urartu genome (AA), therefore showing close evolutionary genetic relationships (Fig.…”
Section: Comparative Genomics Analysis Of the Pmg16 Genetic Regionmentioning
confidence: 99%
“…Among o cially designated Pm genes (Pm1 to Pm68), 10 genes were cloned and characterized so far. Of them, Pm3/Pm8, Pm2, Pm21, Pm60, Pm5e, Pm41 and Pm1a encode nucleotide-binding domain and leucine-rich repeat (NLR) immune receptors (Yahiaoui et al 2004;Hurni et al 2013;Sánchez-Martín et al 2016;Xing et al 2018;He et al 2018;Zou et al 2018;Li et al 2020;Hewitt et al 2020), and Pm24 encodes a tandem kinase protein (Lu et al 2020). Besides, Pm38 (Lr34/Yr18/Sr57/Pm38 multi-resistance gene) encodes an ABC transporter (Krattinger et al 2009) and Pm46 (Lr67/Yr46/Sr55/Pm46 multi-resistance gene) encodes a hexose transporter (Moore et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation